Optimality Theory in ESL Phonology: A Practice of Final Consonant Clusters from Vietnamese L1 Speakers - Thong Vi Nguyen (Universitas Jambi, Magister Program of English Education Department, 2019)
The present study aims to adopt the Optimality Theory to investigate the strategies of pronouncing the final consonant clusters in English by a group of Vietnamese L1 speakers. Vietnamese is a language without the final consonant clusters; therefore, Vietnamese ESL learners tend to have different strategies to pronounce those. Seven Vietnamese graduate students were employed to record their word-list out-loud reading. Each of the consonants occurring in their pronunciation production was considered as one token to be analyzed. The result shows that Vietnamese ESL learners employ five different strategies to generate the final consonant clusters. After that, by adopting the Optimality Theory, this study provides both faithfulness constraints and markedness constraints for each strategy with the attempt to generalize the cases of the final consonant pronunciation of Vietnamese speakers. This study is significant for ESL teachers to understand how the Vietnamese language affects the ESL learners’ final sound pronunciation